Dependence of CPC cut-off diameter on particle morphology and other factors. Issue 4 (2nd April 2016) - Tuch, Thomas; Weinhold, Kay; Merkel, Maik; Nowak, Andreas; Klein, Tobias; Quincey, Paul; Stolzenburg, Mark; Wiedensohler, Alfred
ABSTRACT: In this investigation, we summarize performance parameters of 24 TSI CPCs model 3772 and 9 TSI CPCs model 3790 determined at the World Calibration Aerosol Centre Physics hosted by the Leibniz Institute for Tropospheric Research. Model 3790 CPCs are basically identical to model 3772 laminar continuous flow type butanol-based CPCs with a modified temperature difference between saturator and condenser. The average 50% detection efficiency for silver particles for 3772 and 3790 instruments was found to be 7.52 ± 0.04 nm and 24.34 ± 0.29 nm (average mobility diameter ± standard deviation), respectively. Small changes of the temperature difference between saturator and condenser cause larger shifts of the 50% detection efficiencies of 3790 CPCs compared to 3772 CPCs. In addition to the known calibration material dependence of the 50% detection efficiencies of 3790 CPCs, we found a dependence on the morphology of the particles used for calibration. In our experiments more spherical particles shifted the 50% detection efficiencies towards larger mobility diameters. Copyright © 2016 American Association for Aerosol Research